SOCIOLOGY OF LAW PERSPECTIVES IN REVIEWING THE EFFECTIVE SOCIAL CONTROL FOR SOCIAL MEDIAS - Juni Netti Mardiani; Nurlaily Nurlaily (Journal of Law and Policy Transformation, 2022)
Law as a means of social control is a process of influencing everyone to behave in accordance with society's expectations of the parties and/or victims who will take steps to become a priority part for restorative justice, except for cases that are and have the potential to be divisive. Therefore, communication ethics in social media must not use harsh, provocative, pornographic, or discriminative words and not to post articles or sites that refer to lies. The use of communication media facilities has now grown so rapidly along with advances in communication technology, where we are faced with many choices to be able to convey/access information both through conventional media such as print media and electronic media and the most developed is social media. This research will use the normative legal method with qualitative analysis. The purpose of this research will relate the sociology of law in the use of social media, the most often used by people is social networking, because this site allows people to create personal web pages that can be directly connected with friends to share information and communication. There needs to be controlled to regulate the use of social media as a means of communication so that unwanted things do not occur.